Measurement of the top quark pole mass using $$ \textrm{t}\overline{\textrm{t}} $$+jet events in the dilepton final state in proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV - Collaboration, Cms; Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Bergauer, Thomas; Chatterjee, Suman; Damanakis, Konstantinos; Dragicevic, Marko; Escalante Del Valle, Alberto; Hussain, Priya Sajid; Jeitler, Manfred; Krammer, Natascha; et al. (Springer Science and Business Media LLC, 2023)
Abstract A measurement of the top quark pole mass $$ {m}_{\textrm{t}}^{\textrm{pole}} $$ m t pole in events where a top quark-antiquark pair ($$ \textrm{t}\overline{\textrm{t}} $$ t t ¯ ) is produced in association with at least one additional jet ($$ \textrm{t}\overline{\textrm{t}} $$ t t ¯ +jet) is presented. This analysis is performed using proton-proton collision data at $$ \sqrt{s} $$ s = 13 TeV collected by the CMS experiment at the CERN LHC, corresponding to a total integrated luminosity of 36.3 fb−1. Events with two opposite-sign leptons in the final state (e+e−, μ+μ−, e±μ∓) are analyzed. The reconstruction of the main observable and the event classification are optimized using multivariate analysis techniques based on machine learning. The production cross section is measured as a function of the inverse of the invariant mass of the $$ \textrm{t}\overline{\textrm{t}} $$ t t ¯ +jet system at the parton level using a maximum likelihood unfolding. Given a reference parton distribution function (PDF), the top quark pole mass is extracted using the theoretical predictions at next-to-leading order. For the ABMP16NLO PDF, this results in $$ {m}_{\textrm{t}}^{\textrm{pole}} $$ m t pole = 172.93 ± 1.36 GeV.
Keywords: electron; data analysis method; p p: scattering; CERN Lab; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; GeV-cms; top: mass: measured; jet: associated production; parton: distribution function; QC770-798; Hadron-Hadron Scattering; Top Physics; Nuclear and particle physics. Atomic energy. Radioactivity; muon; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; info:eu-repo/classification/ddc/530; Hadron-Hadron Scattering; CMS; final state: ((n)jet dilepton); Physics; ddc:530; higher-order: 1; perturbation theory: higher-order; mass: pole; Top Physics; quark antiquark: pair; CERN LHC Coll; top: pair production; channel cross section: measured; p p: colliding beams; experimental results